Effects of Mindfulness-Based Positive Behavior Support (MBPBS) Training Are Equally Beneficial for Mothers and Their Children With Autism Spectrum Disorder or With Intellectual Disabilities - Singh, Nirbhay N.; Lancioni, Giulio E.; Karazsia, Bryan T.; Myers, Rachel E.; Hwang, Yoon-Suk; Anālayo, Bhikkhu (Frontiers in Psychology, 2019)
Parenting a child with autism spectrum disorder (ASD) or intellectual disabilities (ID) can be stressful for many parents. Mindfulness-Based Positive Behavior Support (MBPBS) is a customized mindfulness program that enables parents and other caregivers to reduce their perceived psychological stress to normative levels through mindfulness procedures and to support children with ASD or ID to self-manage their challenging behaviors through positive behavior support. In this study, we evaluated whether MBPBS would have differential effects on the stress levels of mothers of adolescents with ASD (n = 47) or with ID (n = 45) and the effects of the program on the aggressive, disruptive and compliance behaviors of their children. Both groups of mothers participated in the 40-week study (10 weeks control and 30 weeks MBPBS program), rated their own stress levels, and collected daily observational data on the adolescents’ behavior. Results showed significant reductions in the level of stress in both groups of mothers, but no differential effects on mothers of children with ASD or with ID. In addition, significant reductions in aggression and disruptive behavior and increases in compliance behaviors were observed in the adolescents in both groups. The results suggest that MBPBS is equally beneficial for mothers of adolescents with ASD or ID. In the present study, although the mothers of children with ID had slightly higher levels of stress at baseline and mothers of children with ASD had lower levels of stress following the MBPBS program, the program can be considered equally effective in reducing the stress levels of both groups of mothers. This suggests the program may be effective regardless of baseline levels of mothers’ stress.